2016
DOI: 10.1021/acscentsci.5b00344
|View full text |Cite
|
Sign up to set email alerts
|

Sea Spray Aerosol Structure and Composition Using Cryogenic Transmission Electron Microscopy

Abstract: The composition and surface properties of atmospheric aerosol particles largely control their impact on climate by affecting their ability to uptake water, react heterogeneously, and nucleate ice in clouds. However, in the vacuum of a conventional electron microscope, the native surface and internal structure often undergo physicochemical rearrangement resulting in surfaces that are quite different from their atmospheric configurations. Herein, we report the development of cryogenic transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 65 publications
7
104
0
Order By: Relevance
“…Such variation, even for a simple 1 : 1 mixture, will result in a range of hygroscopic behaviors when interrogated on a single particle level. 28 Table 2 summarizes OVFs and hygroscopicity parameter, k at RH = 85% (see ESI † for details on calculating the hygroscopicity parameter) determined using AFM for NaCl : glucose and NaCl : laminarin at different mass ratios where a core-shell morphology was observed. The results demonstrate that the ratio of two compounds in solution does not correspond with that observed for the individual particles and depends on the nature and extent of solubility of the organic constituents.…”
Section: Interactions Of Water Vapor With Mixtures Of Sodium Chlormentioning
confidence: 99%
See 1 more Smart Citation
“…Such variation, even for a simple 1 : 1 mixture, will result in a range of hygroscopic behaviors when interrogated on a single particle level. 28 Table 2 summarizes OVFs and hygroscopicity parameter, k at RH = 85% (see ESI † for details on calculating the hygroscopicity parameter) determined using AFM for NaCl : glucose and NaCl : laminarin at different mass ratios where a core-shell morphology was observed. The results demonstrate that the ratio of two compounds in solution does not correspond with that observed for the individual particles and depends on the nature and extent of solubility of the organic constituents.…”
Section: Interactions Of Water Vapor With Mixtures Of Sodium Chlormentioning
confidence: 99%
“…7,10,[16][17][18][19][20][21][22][23][24][25][26] Notably, SSA particles also serve as a means of transporting biological marine microorganisms from the sea to the atmosphere. 20,27 For example, Patterson and coworkers 28 detected the presence of microorganisms such as bacteria, diatoms, virus particles, and marine membrane vesicles in SSAs using cryogenic transmission electron microscopy (cryo-TEM).…”
Section: Introductionmentioning
confidence: 99%
“…To challenge the assumption of a uniform coating, the morphology of the uncoated and coated particles was explored using CRYO-TEM which has recently been shown to be a very promising technique for investigation of nascent sea spray particles (Patterson et al, 2016).…”
Section: Fatty Acid Coatingmentioning
confidence: 99%
“…305 In support of this proposed mechanism are co-located data from IMPACTS, particularly work by Cochran et al 105 that reported more surface active species (e.g. short chain fatty acids) in fine SSA and Patterson et al 268 that reported the incorporation of biological structures and POM into larger SSA particles. Future studies into the dissolved versus particulate nature of these saccharides can aid in clarifying this mechanism.…”
Section: Saccharide Dynamics and Enrichment During The Mesocosmmentioning
confidence: 83%
“…phytoplankton, bacteria and virus), their products (e.g. bacteria vesicles) and detritus, 79,[268][269][270] proteinaceous material, 79,271 transparent exopolymers, 271 polysaccharides, 79,272 fatty acids, 273 alkanes, 273 organic anionic surfactants, 105 and sterols. 274 There is mounting evidence that phytoplankton, bacteria, and viruses in the marine microbial loop modify the composition of SSA by altering the pool of organic material in the ocean.…”
Section: Introductionmentioning
confidence: 99%